The role of livestock portfolios and group-based approaches for building resilience in the face of accelerating climate change: An asset-based panel data analysis from rural Kenya - Marther W. Ngigi; Ulrike Mueller; Regina Birner (University of Bonn, Center for Development Research (ZEF), 2015)
This study examines the impact of multiple shocks on assets by employing two waves of a panel data set of 360 rural households in three agro-ecological zones in Kenya. To control for unobserved heterogeneity, a "within" household fixed effects model was employed. One major finding is that climatic shocks negatively affect households livestock holdings - apart from small ruminant and non-ruminant livestock due to their higher adaptive capacity. Consequently, households rely on two major coping strategies to smooth their consumption level: (1) adjusting their livestock portfolios, and (2) borrowing from group-based approaches. The latter strategy is particularly important for poor households in safeguarding their already low asset base. The findings suggest that livestock protection policies, such as diversification of livestock portfolios, promotion of fodder banks and index-based livestock insurance, are substantial. Scaling-up of group-based approaches would augment poor households recovery and resilience against multiple shocks in the face of accelerating climate change.
Keywords: C33; D13; I18; O12; O13; Q54; 330; multiple shocks; livestock; group-based approaches; rural Kenya